Determination of mycotoxins and their dietary exposure assessment in pale lager beers using immunoaffinity columns and UPLC-MS/MS - Martiník, Jan; Boško, Rastislav; Svoboda, Zdeněk; Běláková, Sylvie; Benešová, Karolína; Pernica, Marek (Mycotoxin research, 2023)
The use of contaminated raw materials can lead to the transfer of mycotoxins into the final product, including beer. This study describes the use of the commercially available immunoaffinity column 11+Myco MS-PREP® and UPLC-MS/MS for the determination of mycotoxins in pale lager-type beers brewed in Czech Republic and other European countries. The additional aim of the work was to develop, optimize and validate this analytical method. Validation parameters such as linearity, limit of detection (LOD), limit of quantification (LOQ), precision and accuracy were tested. The calibration curves were linear with correlation coefficients (R2 > 0.99) for all mycotoxins under investigation. The LOD ranged from 0.1 to 50 ng/L and LOQ from 0.4 to 167 ng/L. Recoveries of the selected analytes ranged from 72.2 to 101.1%, and the relative standard deviation under conditions repeatability (RSDr) did not exceed 16.3% for any mycotoxin. The validated procedure was successfully applied for the analysis of mycotoxins in a total of 89 beers from the retail network. The results were also processed using advanced chemometric techniques and compared with similar published studies. The toxicological impact was taken into account.
Keywords: pivo; Chromatography, High Pressure Liquid; Mycotoxins; Beer; vysokoúčinná kapalinová chromatografie; Tandem Mass Spectrometry; chromatografie kapalinová; Dietary Exposure; mykotoxiny; tandemová hmotnostní spektrometrie; dietární expozice; Chromatography, Liquid